Environmental endocrine disruptors and endometrial cancer: a systematic review of epidemiological studies - Incognito, Dalila; Gelsomino, Claudia; Picone, Antonio; Ettore, Giuseppe; Ettore, Carla; Incognito, Giosuè Giordano; Di Mauro, Giordana; Santarpia, Mariacarmela; Aguennouz, M’Hammed; Parisi, Silvana; Ciappina, Giuliana; Berretta, Massimiliano (Frontiers in Endocrinology, 2026)
Endometrial cancer (EC) is a hormone-dependent malignancy whose global incidence is steadily rising. Increasing evidence suggests that exposure to endocrine-disrupting chemicals (EDCs) may contribute to EC development through interference with hormonal signaling mediated by estrogen receptors (ER). This systematic review aimed to synthesize the available epidemiological evidence on the association between exposure to EDCs and the risk of EC. A comprehensive search of MEDLINE, EMBASE, Scopus, the Cochrane Library, and ClinicalTrials.gov was conducted up to April 2025, following PRISMA 2020 recommendations. Eligible studies included observational or interventional designs assessing quantified exposure to EDCs and EC incidence or risk. Eight studies met the inclusion criteria (five case-control, two cohort, and one randomized controlled trial), comprising 2, 609 EC cases and 1, 577 controls. Cadmium emerged as the EDC most frequently associated with EC, reported in five studies, four of which demonstrated a significant positive association, particularly among lean postmenopausal women. In contrast, evidence regarding bisphenol A (BPA) and its metabolites was inconsistent: only mono-n-butyl phthalate (MnBP) showed a positive correlation with EC in one study, while BPA and dibutyl phthalate (DBP) did not. Nonylphenol and octylphenol were also found to be positively associated with EC risk in a single study. Conversely, neither lead exposure nor dietary intake of isoflavones was associated with EC incidence. Overall, available epidemiological evidence supports a potential association between cadmium exposure and increased EC risk, while data for other EDCs remain limited and inconclusive. Substantial heterogeneity in exposure assessment, study design, and confounder adjustment limits comparability across studies and precludes definitive conclusions. Further well-designed longitudinal studies with standardized and repeated exposure measurements are needed to clarify causal relationships between EDC exposure and endometrial carcinogenesis.Systematic Review Registrationhttps://inplasy.com/inplasy-2025-6-0030/, identifier INPLASY202560030.